Results-Based Financing for Health in Argentina The Plan Nacer Program - Cortez, Rafael (Health, Nutrition and Population (HNP) Discussion Papers, 2012)
The plan nacer program was designed by the Argentine ministry of health to provide health coverage to uninsured women during their pregnancies and for an additional 45 days after giving birth, as well as to children under the age of six. In doing so, it focuses on the most vulnerable populations, addressing a basic inequity in health care. In addition, the program includes three main distinctive features: an explicit menu of health benefits, disbursements linked to achieving agreed-upon targets of enrollment and health results, and audits conducted by an independent external firm to corroborate service delivery and quality. The plan is an innovative way to strengthen health systems. Rather than simply funding more facilities and inputs or adjusting existing insurance mechanisms neither of which have been successful in dealing with the health problems of the poor, the Argentine ministry of health realized that improvements to quality and coverage of health services for the uninsured would require drastic operational changes. To do so, it decided to introduce performance incentives at all levels and to focus on results